Формування інформаційної бази для аналізу і контролю фінансового стану підприємства за метіріалами ПрАТ «Концерн Хлібпром» - Мазурок, Олена Русланівна; Mazurok, Olena Ruslanivna (Ірпінь, 2024)
У кваліфікаційній роботі розглянуто формування інформаційної бази для здійснення аналізу і контролю фінансового стану підприємства та дослідженні проблем і визначенні факторів, які негативно впливають на фінансову стійкість підприємства. За результатами дослідження сформульовані пропозиції, які полягають у формуванні обліково-аналітичного забезпечення ПрАТ «Концерн Хлібпром» для контролю та аналізу фінансового стану, розробці рекомендацій щодо напрямів проведення контрольних заходів та аналізу фінансового стану.

The formation of an information base for implementation of analysis and control of the financial state of the enterprise and investigation of problems and identification of factors that negatively affect the financial stability of the enterprise. According to the results of the research, proposals were formulated, which consist in the formation of accounting and analytical support for PrJSC "Concern Khlibprom" for control and analysis of the financial situation, development of recommendations on the directions of conducting control measures and analysis of the financial condition.
Forming of informative base is for an analysis and control of private joint-stock company business «Concern Khlibprom»
Keywords: інформаційна база; фінансовий стан; обліково аналітичне забезпечення; бухгалтерський облік; фінансова звітність; аналіз і контроль фінансового стану; informative base; financial state; registration-analytical providing; record-keeping; financial reporting; analysis and control of the financial state